Financial Performance Analysis Of Islamic Banks And Conventional Banks: A Comparative Study UNPAB - Marlina, Marlina; Andalkris Yuliasih Laia; Sondang Lastiur Hutahean; Afifah Syahril; Fitri Yani Panggabean (INFOKUM, 2025)
The financial performance of banking institutions plays a crucial role in ensuring economic stability and growth. This study aims to compare the financial performance of Islamic banks and conventional banks in Indonesia by analysing key financial indica-tors such as profitability, liquidity, solvency, and efficiency. Using financial ratio analy-sis (ROA, ROE, CAR, NPF/NPL, and FDR/LDR), this research examines the differences in financial performance between Islamic and conventional banks over a specific period. The study applies quantitative methods with secondary data collected from financial statements of selected banks. The data is analysed using descriptive statistical methods and comparative analysis. The findings indicate that Islamic banks and conventional banks exhibit significant differences in certain financial ratios. Islamic banks tend to have higher capital adequacy and lower non-performing financing (NPF), indicating stronger financial resilience. However, conventional banks generally have higher profita-bility ratios (ROA & ROE), suggesting greater efficiency in profit generation. This study contributes to the literature by providing insights into the strengths and weaknesses of both banking systems. The results are useful for policymakers, investors, and banking professionals in understanding the financial sustainability and risk profiles of Islamic and conventional banks in Indonesia.